Microeconomic theory and functions - Holland, Thomas Edward (New York : Appleton-Century-Crofts, 1973)
This textbooks contains an introductory-level presentation of microeconomics theory, including functional concept to economic problems of resources allocation.
Includes bibliographical references.
asm 22/01/2019
Loans
Keywords: Microeconomics